Convocation of shareholders meeting - Arsić, Zoran (Zbornik radova Pravnog fakulteta u Novom Sadu, 2013)
Convocation of shareholders meeting is a sort of comunication among shareholders and company determined by kinds of shares regulated in each national legal system. As a rule shareholders with registered shares are to be notified individually, while existence of bearer shares requires public announcement. Despite lack of bearer shares in domestic law, Serbian Company Act stipulates both techniques.